Skills or jobs: Which comes first? - Jesko Hentschel (IZA World of Labor, 2017)
Skills are widely regarded as being necessary for boosting productivity, stimulating innovation, and creating new jobs, while skill mismatches are often cited as being responsible for a lack of dynamism in the labor market. However, heavy investments in technical and vocational training programs are seldom a “silver bullet.” Recent evidence on skill building not only points to the core importance of foundational skills (both cognitive and social) for success in the labor market, but also emphasizes how jobs themselves can lead to learning and shape social competencies that, in turn, ignite innovation and create more jobs.
Keywords: J24; 330; skill formation; skill mismatch; knowledge spillovers